Delayed Abscopal Response 3 Years After Robotic Stereotactic Body Radiation Therapy for Renal Cell Carcinoma: A Case Report - Zhe Chen; Toshihiro Suzuki; Zennosuke Mochizuki; Hiroshi Takahashi; Kan Marino; Takafumi Komiyama; Hiroshi Onishi (Cancer Reports)
ABSTRACT Background Renal cell carcinoma (RCC) is the most common malignant tumor of the kidney in adults, with poor prognosis in advanced or metastatic stages. Although traditionally considered radioresistant, RCC has shown a promising response to stereotactic body radiation therapy (SBRT), which not only offers local tumor control but may also induce an abscopal effect, resulting in regression of distant metastases. Case A 54‐year‐old male with a history of right RCC underwent radical nephrectomy in 2000, followed by partial nephrectomy for a left kidney recurrence in 2005. In 2011, imaging revealed a second recurrence in the left kidney. In 2013, after declining further surgery, he was treated with SBRT for the recurrent left renal lesion. Follow‐up imaging revealed a stable renal mass and a solid right lung nodule. Retrospective analysis of prior imaging suggested the presence of pulmonary metastases concurrent with the renal recurrence. The pulmonary nodule progressively enlarged until November 2016 but then spontaneously regressed by November 2017 without any additional systemic or local interventions, and remained stably reduced in size thereafter. Serial imaging from 2018 showed no evidence of new metastatic disease, and the left renal lesion exhibited partial regression. The pulmonary metastasis remained stable, consistent with the occurrence of an abscopal effect that persisted for 3 years. The patient ultimately passed away in 2024 from unrelated causes. Conclusion This case demonstrates the potential of SBRT to induce a systemic abscopal response in metastatic RCC, with sustained control of pulmonary metastasis over 3 years. The findings suggest that SBRT may play a critical role in managing metastatic RCC, warranting further research into its synergy with immunotherapy for long‐term therapeutic benefit.